Pengaruh Latihan Motor Ability Terhadap Kemampuan Teknik Dasar Dalam Ekstrakurikuler Taekwondo Siswa Sekolah Menengah Atas - Annisa Juliana Djaffar; Febi Kurniawan; Ega Trisna Rahayu (Peneliti.net, 2022)
In this study aims to determine and analyze in hypothesis testing regarding the Effect of Motor Ability Exercise on Basic Technical Ability in Taekwondo Extracurricular SMAN 1 Pusakanagara. The approach used in this research is a approach quantitative and for the method in the form of experiments. For population and sample in this study were 12 students who took extracurricular. Instruments that used in this study in the form of a Motor Ability Test which will later used as an exercise concept to determine students' motor skills. Data processing in this study was assisted by using the SPSS application by using the SPSS application normality test formula (Kolmogorov-Smirnov), homogeneity test and t-test in pairs. From the calculation, it can be concluded that the six items tested all have significant value. On Normality Test (Kolmogorov-Smirnov) all are normally distributed with a value > 0.05. In the homogeneity test, performed calculations and the results on the same sample variance (homogeneous). In the paired t-test of the hypothesis in this study the results are H0 which means The Effect of Motor Ability Training on Basic Technical Ability In Taekwondo Extracurricular SMAN 1 Pusakanagara.